Billions: Season Four season four - Koppelman, Brian; Levien, David; Sorkin, Andrew Ross; Giamatti, Paul; Lewis, Damian, 1971-; Siff, Maggie, 1978-; Showtime Entertainment; Paramount Home Entertainment (Firm) (Los Angeles, CA : Paramount Home Entertainment, 2019)
Former enemies Bobby Axelrod and Chuck Rhoades, and Wendy Rhoades, the chief counselor to each, have come together to form an uneasy but highly effective alliance, aimed at the eradication of all their rivals.
Disc 1. Chucky Rhoades's greatest game -- Arousal template -- Chickentown Disc 2. Overtone window -- A proper sendoff -- Maximum recreational depth Disc 3. Infinite game -- Fight night -- American champion Disc 4. New year's day -- Lamster -- Extreme sandbox.
Originally broadcast as single episodes of a television program in 2019.
Special features: Pick a side ; Inside fight night ; Script to screen ; Billions references.
new dvd 2024 winter.
Paul Giamatti, Damian Lewis, Maggie Siff, Toby Leonard Moore, David Costabile, Condola Rashad, Asia Kate Dillon, Jeffrey DeMunn, Kelly AuCoin, John Malkovich.
TV rating: TV-MA.
DVD, NTSC, region 1; wide screen; Dolby digital 5.1.
Keywords: United States. -- Attorney (New York : Eastern District) -- Drama; Capitalists and financiers -- New York (State) -- New York -- Drama; Commercial crimes -- Investigation -- New York (State) -- New York -- Drama; Television series; Fiction television programs; Legal television programs; Television programs for the hearing impaired; Crime television programs